Pelaksanaan Perlindungan Konsumen Obat-Obatan dalam Kefarmasian - I Putu Rusdi Eka Pratama; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2021)
Technological advances have helped in the discovery of the latest medicines, this has further strengthened healthcare providers. However, this is not the case with consumers (patients). Consumers are less aware of their rights as users of goods and services so that which ones are good and which are bad, and which are really needed, consumers leave completely to competent health workers. This study aims to explain the legal protection of drug consumers for pharmaceutical services and to explain the liability of pharmaceutical companies regarding the losses suffered by drug consumers. This research used empirical law. Primary data sources were obtained by conducting field research with interview techniques and secondary data obtained by library research consisting of primary and secondary legal materials. The results showed that the legal protection of drug consumers in pharmaceutical services, which contains the rights and obligations of consumers as well as the rights and obligations of pharmaceutical companies as business actors. In principle, consumer legal protection is regulated in Law Number 8 of 1999 concerning Consumer Protection, in practice in pharmacies, legal protection for drug consumers is in accordance with applicable regulations and has been effective and conducive, then the responsibility of pharmaceutical companies for consumer losses drugs have provided compensation for material and immaterial damages when consumers are harmed.